(untitled) (Confluenţe Bibliologice, 2012)
The article presents information about the professional Standard Application workshop "Performance Indicators for libraries"- ISO 11620: 2008, IDT and eﬃciency educational library organized on 16 May 2001 by the Ministry of Education of the Republic of Moldova, Branch School Libraries in the North of Moldova (BSLNM) of library Association of Republic of Moldova with residence in Scientiﬁc Library of "Alecu Russo” State University from Balti. The event brought together about 40 school librarians, college and professional schools, responsable specialists for the work of school library activities in the Northern part of R. Moldova, university librarians. The program included 15 communications in 3 modules: Management, Information Technology.